Modern ways of designing roads through urban areas - Čarský, Jiří; Mačerinskienė, Aida (Journal of Civil Engineering and Management, 2003)
An important part of forming traffic plans is through designing better traffic conducting. The through roads in urban areas are places of great traffic importance and the concentration of traffic can create serious problems. Solving of this problem significantly influences the future position and functions of current through roads in urban road networks as well as creating the possibilities of new traffic and technical organisation. The purpose of the process of the formation of modern and traffic easing on through roads is to reach better safety levels for all road users, improving pedestrian and cyclist conditions, optimising the used traffic spaces, improving the aesthetic standards of the through roads and slowing down the environmental impact of air pollution and traffic noise. For this purpose the new methodology defines a large number of project elements and specifies the possibilities of its use. It should support new ways of thinking in the designing of through roads and traffic easing, because the implementation of modern European trends is necessary in Lithuania. Firstly it is necessary to choose the optimal road speed and maximum speed limits. The suitable speed limit will depend on the traffic volume, on the number of pedestrians and cyclists and on the surroundings characteristics. Traffic easing elements on through roads generally do not cause a decline of capacity, but under specific conditions it can increase them. The use of particular elements and disposals depends on the place, eg where different elements are recommended to be placed before entry into any town/village, on the town/village’s entry or in the use of through roads inside a town/village. Among the most used project elements in traffic easing on through roads, belong changes for the better modification of cross-sections and parking lanes, the implementation of middle traffic islands, local bottlenecks of traffic lanes, modification of crossings for pedestrians and the use of small roundabouts and finally under limited conditions and the use of traffic humps. First Published Online: 26 Jul 2012